The impact of “To Err Is Human” on patient safety in anesthesiology. A bibliometric analysis of 20 years of research - Neuhaus, Christopher; Grawe, Petra; Bergström, Johan; St.Pierre, Michael (Frontiers in Medicine, 2022)
Background: Patient safety gained public notoriety following the 1999 report of the Institute of Medicine: To Err is Human – Building a Safer Health System which summarized a culminated decades’ worth of research that had so far been largely ignored. The aim of this study was to analyze the report’s impact on patient safety research in anesthesiology. Methods: A bibliometric analysis was performed on all anesthesiologic publications from 2000 to 2019 that referenced To Err Is Human. In bibliometric literature, references are understood to represent an author’s conscious decision to express a relationship between his own manuscript and the cited document. Results: The anesthesiologic data base contained 1.036 publications. The journal with the most references to the IOM report is Anesthesia & Analgesia. By analyzing author keywords and patterns of collaboration, changes in the patient safety debate and its core themes in anesthesiology over time could be visualized. The generic notion of “error”, while initially a central topic in the scientific discourse, was subsequently replaced by terms representing a more granular, team-oriented, and educational approach. Patient safety research in anesthesia, while profiting from a certain intellectual and conceptual head start, showed a discursive shift towards more managerial, quality-management related topics as observed in the health care system as a whole. Conclusions: Over the last 20 years, the research context expanded from the initial focus set forth by the IOM report, which ultimately led to an underrepresentation of research on critical incident reporting and systemic approaches to safety. Important collaborations with safety researchers from outside of health care dating back to the 1990s were gradually reduced, while previous research within anesthesiology was aligned with a broader, more managerial patient safety agenda.